EFEKTIVITAS PEMIDANAAN NARAPIDANA PELAKU PEREDARAN NARKOTIKA JARINGAN LEMBAGA PEMASYARAKATAN DI KOTA BENGKULU - Pradityo, Randy; Jayanuarto, Rangga; Pradeva, Yozie; Susiyanto, Susiyanto (Solusi, 2021)
Drug trafficking is an extraordinary crime. Circulation of narcotics is not only carried out by international, national scale networks, but is also carried out by prisoners in the Correctional Institution as perpetrators of trafficking. This study will measure the effectiveness of punishment against inmates who are perpetrators of narcotics trafficking in the Correctional Institution network in Bengkulu City. The results of this study indicate that the punishment of inmates who commit narcotics trafficking in the prison network has not been effective. Many factors have caused it to be ineffective, the most important of which is the number of inmates who are perpetrators of narcotics trafficking, the prison network continues to grow, while special prisons for narcotics cases are not yet available. Then, from the aspect of implementation and supervision of punishment in the Correctional Institution, it has not been carried out optimally due to limited human resources, both in quality and quantity. Convicts become perpetrators of narcotics trafficking in Correctional Institutions due to various things. For example, there is an influence from the environment of fellow prisoners who are perpetrators of narcotics trafficking in the Correctional Institution, as well as due to the economic factors of the prisoners.